The well-being, peer cultures and rights of children - Bass, Loretta Elizabeth; Kinney, David A., 1960- (Bingley, U.K. : Emerald, 2011)
This volume is comprised of empirical research and theoretical papers within three key areas, namely childrens well being, children and youth peer cultures, and the rights of children and youth. These empirical studies include childrens voices and experiences from four continents (Asia, Europe, North America and South America) and a range of methodological and theoretical orientations. A clear connection to social policy at a national and international level is made in many of these studies. Topics are wide-ranging and include: Praetorian militarization; school mobility; math and reading achievement gaps; dating and the developmental discourse in a summer camp; and school and social exclusion for urban young people. Altogether, these studies highlight how structure and culture both limit and enable the life chances of children, how children interpret and construct their social relations and environments, and how children view themselves as well as how others view the rights of children. This volume is a further example of how the Sociological Studies of Children and Youth series successfully showcases major strands of current thinking on children and youth in our world today.
Praetorian militarization and children's life chances / Steve Carlton-Ford -- School mobility, social capital, and educational experiences of Latino foster care youth / Beatrix F. Perez, Harriett D. Romo -- Math and reading achievement gaps : new insights to old problems / Yingyi Ma -- Focused : how students construct attentiveness in first-grade classrooms / Noriko Milman -- The age of love : dating and the developmental discourse in a middle school summer camp / Sandi Kawecka Nenga, Lauren A. Apgar -- New avenues to school exclusion and social exclusion for urban young people in the UK / Daniel Briggs -- Constructing alternative femininity : the gender identity of 'bad girls' in Taiwan / Yu-Hsuan Lin -- Applying the 'new' sociology of childhood to explain the black-white test-score gap / Sarah H. Matthews -- Waiving parental consent when researching at-risk youth / Timothy Stablein, Steven H. Jacobs -- Remembering the child patient / Renee Hosang -- Participation and protection of youngsters with serious behavior problems in Norwegian child welfare services / Ingeborg Marie Helgeland -- Do ECE public policies consider young children's agency? : a study in São Paulo, Brazil / Maria Letícia Nascimento -- Political and legal effects of the convention on the rights of the child in Latin American countries / Maria Guiomar da Cunha Frota.
Mode of access: World Wide Web.
Print version record
Keywords: Social Science -- Sociology -- General; Social Science -- Children's Studies; Social Science -- General; Sociology; Social issues (Children's/YA); Child development; Sociology